Isolation and Detection of Bacterial Strains from Cosmetics Products available in Pakistan: Bacterial Strains from Cosmetics Products - Tazeen; Sidra Rahman; Rizwan Abbas; Syed Ahsan Shahid; Zabta Khan Shinwari; Muhammad Ali (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Cosmetics products are the most essential and frequently used components in our daily life. Besides improving human health, they provide healthy lifestyles and boost our self-esteem. Globally cosmetics market is projected to be 287 billion USD in 2021 to 415 billion USD in 2022. This research study aims at the isolation, identification, and characterization of bacterial strains isolated from cosmetics. Six bacterial colonies were isolated by inoculating different cosmetics products on tryptic soya agar media. All the strains showed optimum growth at 37 °C. All strains were assessed through biochemical tests by using different media such as MacConkey agar, SIM, and Simmons citrate agar and were further proceeded for nucleotide sequencing through Sanger sequencing. Different bacterial strains were revealed in cosmetics products including Sphingomonas paucimobilis, Cytobacillus oceanisediminis, Robertmurraya andreesnii, Cytobacillus firmus, Falsibacillus pallidus, and Acinetobacter junii. Most of these strains were found to be pathogenic however, Sphingomonas has the potential for bioremediation and can be utilized for degrading toxic compounds to make the environment better. Similarly, Cytobacillus is found to be involved in biomineralization and also aids in fermentation. Our results have shown that there is a dire need to assure strict safety regulations regarding cosmetics. Improper manufacturing practices can lead to the contamination of cosmetics which could lead to severe consequences of deteriorating the quality of health. Further studies are needed to explore the potential of these isolates so that they can be utilized to improve our health as well as the environment.